Development of Integrated Thematic Student Worksheets (LKPD) Using the Discovery Learning Model in Class IV Elementary Schools - Melindawati, Silfi (CV. Inara, 2020)
This research is motivated because of the problems found in schools, namely, the LKPD used in schools is generally less attractive, both in terms of the space for filling in the less extensive answers, the color of the LKPD which does not have an attractive color, the structure is incomplete and the supporting images for the LKPD are inadequate. This research is a development research, namely Research and Development (R&D) which consists of four stages, namely: define, design, development, disseminate. in this development research using the 4-D model proposed by Thiagarajan (in Ratumanan, 2019: 61). The results showed that the development of discovery learning-based LKPD collected through a validation questionnaire was used to measure the feasibility of student worksheets (LKPD). The results showed that the discovery learning-based student worksheets developed were feasible and valid for learning. This is evident from the results of obtaining questionnaires by expert experts and educators who state that the development product is feasible based on the results of the linguist expert's validity test (92.5%) is categorized as very valid, aspects of rpp Validator 1 (92.5%) are categorized as very valid, Validator 2 (95.00%) which is categorized as very valid, expert design expert (98.07%) is categorized as very valid. This proves that the Integrated Thematic Student Worksheet Development (LKPD) with the Discovery Learning Model in Class IV of Elementary School is stated very valid.